Potential for climate change adaptation and mitigation in crop production in East Africa: Findings from a scoping study on opportunities and barriers to adaptation and mitigation in crop value chains of Kenya, Tanzania and Uganda - Osumba, Joab J.L.; Recha, John W.M.; Demissie, Teferi Dejene; Shilomboleni, Helena; Radeny, Maren A.O.; Solomon, Dawit; Mungai, Catherine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Agricultural production in East Africa is mainly rain-fed, making it highly sensitive and vulnerable to increased climate variability arising from climate change (EAC 2017a). Climate vulnerability is also exacerbated by reduced produce quality, land degradation, declining soil fertility and imperfect insurance and credit markets. Smallholder farming systems in the region are characterized by low productivity and commercialization (EAC 2017b).